Public Participation as a Manifestation of Deliberative Democracy in the Drafting of Regional Regulations: Between Normative Ideality and Empirical Practice - Satria, Indah; Jamaludin Ghofur (As-Siyasi: Journal of Constitutional Law, 2026)
Public participation in the drafting of regional regulations (Peraturan Daerah) is a fundamental element in realizing a strongly legitimate local democracy. Normatively, the Indonesian legal system has recognized and regulated the right of public participation in the regional legislative process through Law Number 12 of 2011 in conjunction with Law Number 13 of 2022 concerning the Formation of Legislation and Law Number 23 of 2014 concerning Regional Government. However, empirical evidence shows that public participation in drafting regional regulations remains procedural and symbolic, not yet fully reflecting the principles of deliberative democracy. This article aims to critically analyze the normative ideal of public participation in the drafting of regional regulations, the empirical practice of public participation in various regions in Indonesia, and the factors that prevent such participation from becoming a substantive manifestation of deliberative democracy. This research employs a normative juridical method, drawing on legislative, conceptual, and court decision approaches, specifically using Jürgen Habermas's theory of deliberative democracy as the main analytical framework. The study's findings indicate that although the normative framework has opened up space for public participation, its implementation remains dominated by a procedural democratic paradigm that emphasizes formal stages without ensuring the quality of deliberation. Public participation is often limited to consultation forums that lack rational dialogue, are characterized by unequal power relations, and lack adequate feedback mechanisms. As a result, the regional regulations may lose social legitimacy. This article recommends strengthening the institutional design of public participation, oriented toward substantive deliberation, to achieve democratic, responsive, and equitable regional legislation.